THE CONSTRUCTIVIST LEARNING THEORY: EXPLORING KEY TECHNOLOGICAL ADVANCEMENTS IN LEARNING MANAGEMENT SYSTEMS - Zamrin Md Zin; Arman Shah Abdullah; Hanafi Ahmad; Farah Hussan Sahib, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The Constructivist Learning Theory emphasizes learners actively constructing knowledge through experiences and reflection, significantly influencing Learning Management Systems (LMS) design and development, which are pivotal in modern education. This article carefully examines the progress of technology in LMS while looking at it through the perspective of Constructivist Learning Theory, utilizing the PRISMA framework. The review focuses on innovations such as artificial intelligence (AI), machine learning (ML), gamification, mobile learning, learning analytics, and collaborative tools. These technologies have transformed LMS into interactive, personalized, and efficient platforms supporting active learning and knowledge construction. The paper examines how these advancements align with constructivist principles, enhancing student engagement and learning outcomes. Additionally, it addresses the challenges and limitations of implementing these advancements and suggests potential future research directions.